A Study on Consumer Perception with Reference to Third Party Administrators (TPAs) - Sane, Sandip; Singh, Niharika (Indian Journal of Marketing, 2012)
TPA stands for a Third Party Administrator. The TPA is an intermediary between the Insurer and the Customer. TPA's were introduced by the Insurance Regulatory and Development Authority of India (IRDA) in the year 2001. It defines TPA as a, " Third Party Administrator who, for the time being, is licensed by the Authority, and is engaged, for a fee or remuneration, in the agreement with an Insurance Company, for the provision of health services." Since the TPA is performing a task traditionally handled by the company providing the insurance, it can also be seen as outsourcing of the claim settlement process. Customers can directly deal with TPAs at the time of claim and the TPA will help with all the processes of claim settlement. A TPA renders a variety of services like networking with hospitals, arranging for hospitalization, claim processing and settlement. With the advent of so many TPAs in the market, it became very difficult for Insurance companies to choose between them so that they can offload their Claim related work. The study here gives us a comprehensive idea regarding the parameters on which customers prefer any TPA. The study would also help Insurance Companies as well as TPAs to align their resources in such a way so that they can proactively give more impetus to the services which are deemed most important by the customers.